The Effect Of Breathing Relaxation And Lavender Aromatherapy On Insomnia In The Elderly (Interest : Jurnal Ilmu Kesehatan, 2021)
Background: The elderly experience insomnia in the form of problems with symptoms of sleep disorders in the form of repeated difficulties in sleeping or maintaining sleep even though there is an opportunity to sleep. The objective of research was to analyze the effect of Breathing Relaxation Aromatherapy Combination Lavandula Angustifolia on Insomnia in the Elderly. Methods: The design was a pre-experiment with approach the one group pretest-posttest design. The research population was elderly insomnia in elderly Posyandu and the sample was 21 peoples. The sampling research was total sampling. Variabel independent was Breathing Relaxation combination with lavender aromatherapy is relaxation using breathing techniques slowly and deeply, variabel dependen was insomnia level. Statistic test use Wilcoxon Signed Ranks Test Results: The results showed that The Wilcoxon Signed Ranks Test ρ value = 0,000, H1 is accepted, meaning that there is an effect of the Breathing Relaxation and lavender aromatherapy on insomnia in the elderly. The combination of Breathing Relaxation and lavender aromatherapy increases the relaxation response in the elderly. Conclusion: Effect of Breathing Relaxation combination of lavender aromatherapy (Lavandula angustifolia) is more effective in reducing insomnia levels in the elderly and is highly recommended and safe for the elderly)
Keywords: breathing relaxation; elderly; insomnia; lavandula angustifolia; lavender aromatherapy